Access Site Related Vascular Complications following Percutaneous Cardiovascular Procedures - Johanna Hetrodt (MDPI AG, 2021)
Vascular access site complications (ASC) are among the most frequent complications of percutaneous cardiovascular procedures (PCP) and are associated with adverse outcome and high resources utilization. In this prospective study, we investigated patients with postprocedural clinical suspicion of ASC evaluated by duplex ultrasound (DUS) for the presence of ASC. We assessed the incidence, in-hospital outcome, treatment of complications and predictors for ASC. Overall, 12,901 patients underwent PCP during a 40 months period. Of those, 2890 (22.4%) patients had postprocedural clinical symptoms of ASC and were evaluated using DUS. An ASC was found in 206 of the DUS examined patients (corresponding to 7.1% of the 2890 DUS examined patients). In 6.7% of all valvular/TAVI procedures, an ASC was documented, while coronary, electrophysiological and peripheral PCP had a comparable and low rate of complications (1.2–1.5%). Pseudoaneurysm (PSA) was the most frequent ASC (67.5%), followed by arteriovenous fistula (13.1%), hematoma (7.8%) and others (11.7%). Of all PSA, 84 (60.4%) were treated surgically, 44 (31.6%) by manual compression and 11 (7.9%) conservatively. Three (0.02%) patients died due to hemorrhagic shock. In conclusion, femoral ASC are rare in the current era of PCP with PSA being the leading type of ASC. Nonetheless, patients with predisposing risk factors and postprocedural suspicious clinical findings should undergo a DUS to early detect and mitigate ASC-associated outcome.